Kobiety w życiu i twórczości Alojzego Felińskiego - Patro‑Kucab, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The authors of papers dedicated to Alojzy Feliński, while reaching for his works, analyzed above all his Barbara Radziwiłłówna or Hymn na rocznicę ogłoszenia Królestwa Polskiego… Unfortunately, there are no broader discussions of Feliński’s relationships with women within research interests, despite the fact that many episodes addressed to them can be found in the playwright’s work. In the exemplification, the author of the article examines fragments of letters, diaries and poems relating to women who played a special role in the playwright’s life. The purpose of the thesis is not to reveal completely unknown works or events from Feliński’s biography to the reader. The research point of view is primarily an attempt to gather in one publication the works of the Radamist i Zenobia’s author dealing with the women whom the artist met in his life and to whom he did not remain indifferent. These included, among others: Zofia Załęska, Józefa Omiecińska, Emilia and Tekla from the Feliński family and Helena Felińska. The topic seems interesting and definitely deserves wider recognition, because it will present the representative of postanisławowski classicism in a broader and more comprehensive light, yet far from inducing any sensation.